Novel Drug Delivery System: Resealed Erythrocytes (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
To overcome drawbacks of conventional drug delivery system, modern drug delivery approach such as resealed erythrocytes can be a potential delivery system. Resealed RBC's are biodegradable, biocompatible and have prolonged life cycle. A number of mammalian RBC’s are being utilized in drug encapsulation and resealing for their utilization in enzyme and drug delivery. Resealed erythrocytes can be used for drug targeting, carrier for drug, enzyme, macromolecules and proteins. For getting drug loaded erythrocytes collect the sample of blood, then separate erythrocyte from plasma; then loading of drug into erythrocyte and the resulted drug loaded erythrocytes resealed.There are different methods of drug loading such as dialysis method, dilution method, endocytosis method etc.The survival time of RBC is dependent on the shape, size, senescent cells antigen, surface charge and haemoglobin content lost at the time of loading. The survival time decide their entrapment efficiency. Resealed RBC's have potential treatment in hepatic tumour, parasitic disease, removal of toxic agents, replacement therapy, oxygen deficiency therapy. Therefore, resealed can be better delivery method for target  drug delivery.